Tunable graphene-based plasmonic waveguides: nano modulators and nano attenuators - Huang, Xu Guang (2014)
A modulation principle and method, the gate-voltage-controlled mode-guiding switching/mode-cutoff mechanism, is proposed and numerically investigated to achieve the modulation/attenuation function. The propagating attenuation of the graphene 2D waveguide as a function of the Fermi level of the cladding is analyzed. Different modes with low or high attenuations in a wide attenuation range have been observed. The proposed structure avoids the patterning on graphene or substrate, thus diminishing the energy scattering on the edges. It also has the advantages of large modulation depth/attenuation range, wide bandwidth, and sub-micrometer chip-length with a nanoscale lateral section, which is promising for future graphene-based integrated photonic devices.